P190 QVA149 Once Daily Provides Significant Improvements in Lung Function Over 1 Year in Patients with COPD: The Enlighten Study. (19th November 2012) - Dahl, R; Chapman, K; Rudolf, M; Mehta, R; Kho, P; Alagappan, V; Berhane, I; Chen, H; Banerji, D
Abstract : Introduction: QVA149 is a novel inhaled once-daily dual bronchodilator, containing a fixed-dose combination of the long-acting β2 -agonist indacaterol and the long-acting muscarinic antagonist NVA237 (glycopyrronium) in development for the treatment of COPD. This study evaluated the long-term effect of QVA149 on lung function in patients with COPD. Methods: This was a multicentre, double-blind, parallel group, placebo-controlled study in which patients with moderate-to-severe COPD were randomised (2:1) to receive QVA149 (110/50µg) or placebo once daily via the Breezhaler® device for 52 weeks. Treatment was taken in the morning at the same time of day. Lung function was measured as forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) at 30 and 60 minutes post-dose at clinic visits over 52 weeks. Results: 339 patients (77% male, mean age 63 years; mean post-salbutamol FEV1 57% predicted, FEV1/FVC 54%) were randomised to receive QVA149 (n=226) or placebo (n=113); 86% and 79% of patients respectively completed treatment, respectively. QVA149 significantly increased FEV1 and FVC versus placebo at all assessment points (table ). Conclusion: QVA149 once daily provided rapid and clinically meaningful bronchodilation compared with placebo. No tachyphylaxis was observed and the bronchodilator effect was sustained over the 52 week treatment period. Ronal Dahl: he participated in advisory boards for Novartis, AstraZeneca, Boehringer-Ingelheim, Pﬁzer, ALK-Abello, UCB, Nycomed, Dainippon and ONO. Kenneth R Chapman: he holds the GSK-CIHR Research Chair in Respiratory Healthcare Delivery at the University Health Network, has served as a consultant to CSL Behring, GlaxoSmithKline, Novartis, Nycomed (Takeda), and Talecris (Grifols), and has received payment for lectures or service on speakers bureaus from Boehringer-Ingelheim, GlaxoSmithKline, Grifols, Nycomed (Takeda), Family Physicians Airways Group of Canada, Canadian Network for Respiratory Care, and Talecris. Michael Rudolf: he has been reimbursed by the following companies for speaking at educational meetings, for consultancy work, or for attending scientific conferences: Almirall, Astra-Zeneca, Boehringer Ingelheim, Chiesi, GlaxoSmithKline, Merck Sharp and Dohme, Napp, Novartis, Pfizer, Schering-Plough, and Teva. Rajendra Mehta: he has no conflicts of interest.